2012
DOI: 10.1002/hfm.20341
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Company Members' Full Innovative Potential

Abstract: Most of the literature on innovation management highlights the fundamental role played by people in the innovation process and the need to fully develop the creative and innovative potential of organizations' members. This article offers the result of extensive research carried out among some of the most innovative companies in the Basque Country, a highly innovative region located in the north of Spain. It draws interesting conclusions about how these innovative companies combine strong leadership, human reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
2
0
2
Order By: Relevance
“…Amostra: 6341 organizações (meta análise). Velasco et al (2013) Duas amostras: Amostra 1: 150 org. ; Amostra 2: 83 org.…”
Section: Análise Dos Resultadosunclassified
See 1 more Smart Citation
“…Amostra: 6341 organizações (meta análise). Velasco et al (2013) Duas amostras: Amostra 1: 150 org. ; Amostra 2: 83 org.…”
Section: Análise Dos Resultadosunclassified
“…Regressão múltipla, correlação, teste de hipóteses. Velasco et al (2013) Correlação, teste t. Wei et al (2013) Estatística descritiva, correlação, AFC, MEE, teste de hipóteses. Abdullah et al (2014) Estatística descritiva, correlação, AFE, AFC, teste de hipóteses.…”
Section: Análise Dos Resultadosunclassified
“…Leaders must advocate for and establish innovation supportive climates and a knowledge sharing culture within organizations. An organization with a knowledge sharing culture will encourage employees to exchange information across departmental borders, and employees will regard the freedom to share and exchange information as natural (McDermott & O’Dell, ; Velasco, Zamanillo, & Del Valle, ). Similarly, this study also confirmed that leaders’ innovation expectations are positively related to employees’ psychological empowerment and knowledge sharing behavior.…”
Section: Resultsmentioning
confidence: 99%
“…While initial efforts have been made to validate some of the existing instruments as predictive of innovation outcomes, ensure internal reliability (e.g., Brettel & Cleven, ; Chen, ; Sharifirad & Ataei, ), and even compare performance with different groups (e.g., Sušanj, ; Velasco, Zamanillo, & Del Valle, ), few of these instruments—including Rao and Weintraub's () Innovation Quotient instrument—have been replicated and reported in the empirical literature. Estimates of model fit, inter‐item relationships, and reliability for the Innovation Quotient instrument, in particular, have yet to be cited in the literature.…”
mentioning
confidence: 99%